2016
DOI: 10.4028/www.scientific.net/amm.851.751
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Lime Concrete with FRP: An Alternative in the Restoration of Architectural Heritage

Abstract: Abstract. Reinforced concrete has been the material mainly used in the repair of traditional structures of historic buildings. However, since the end of the 20th century, it began to question its use, especially for damages arising from corrosion of steel. An alternative is lime concrete reinforced with Glass Fiber Reinforced Polymer (GFRP) bars. Current lime concrete provides a high compressive strength and prevent problems such as cement alkalinity. GFRP bars provide the necessary tensile strength. Its modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The mechanical properties of wood-modified lime mortars improved by almost 25% in comparison to the reference sample; however, the cohesion of the matrix was problematic. Almerich et al [59] used Glass Fiber-Reinforced Polymer (GFRP) bars as a replacement for steel bars in reinforced lime concrete. It was observed that the lime concrete modified with GFRP had high UCS, acceptable tensile strength, a higher elastic modulus and adhesion, good compatibility, and reduced cement alkalinity.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of wood-modified lime mortars improved by almost 25% in comparison to the reference sample; however, the cohesion of the matrix was problematic. Almerich et al [59] used Glass Fiber-Reinforced Polymer (GFRP) bars as a replacement for steel bars in reinforced lime concrete. It was observed that the lime concrete modified with GFRP had high UCS, acceptable tensile strength, a higher elastic modulus and adhesion, good compatibility, and reduced cement alkalinity.…”
Section: Introductionmentioning
confidence: 99%
“…The lime addition up to 10% did not affect the soundness of the blended cements like PSC and PPC. [30], concluded from their work that lime concrete reinforced with Glass Fibre Reinforced (GFRP) is a viable alternative to replace the reinforced concrete design in the repairs of historical eating. Highest compressive obtained was 14MPa.…”
Section: Introductionmentioning
confidence: 99%